Question Card Game to Improve Senior High School Students' Higher-Order Thinking Skills in Biology Learning - Indria Wahyuni; Mukrimah Mukrimah; Faatihah Nasywaa Hanifah; Julianti Devi Ariesca; Windayanti Windayani (International Journal of Biology Education Towards Sustainable Development, 2022)
Technology development in the world of education will affect the existing curriculum. Whether or not an education is successful depends largely on the curriculum used. The curriculum is the spearhead for the implementation of education. In a curriculum, there are various supporting aspects. One of them is the learning model. Various learning models have been tried to develop student's thinking skills, for example, using the medium of question cards. Playing question card media can trigger direct student involvement in learning to increase high-level thinking skills and motivation to be more active in studying. This research is a Collective Action Research (RAC) study. "activities of planning, acting, observing/evaluating, and reflecting." Students' HOTS ability before applying learning motivation with a class XI student support question card at one of the state high schools in Banten, which obtained an average of 63.89, was then used to calculate the average percentage to determine the level of students' HOTS ability. After an average percentage score of 63.89% is converted to a five-scale LAP, the student's pre-cycle HOTS ability level is relatively low (40-64). Based on data analysis and discussion of the research results that have been described, implementing learning to play question cards can increase student learning motivation and HOTS.